THE INFLUENCE OF MEANINGFUL WORK, CAREER DEVELOPMENT, AND JOB INSECURITY ON THE TURNOVER INTENTION OF PT PATRA JASA EMPLOYEES IN SURABAYA - Adi, Faisal Rahman; Nur, Dhani Ichsanuddin; Anwar, Muhadjir (JURNAL ILMIAH EDUNOMIKA, 2024)
Turnover Intention is a desire of an individual worker to leave or resign from their current workplace and/or to change their place of work. This study aims to examine the Effect of Meaningful Work, Career Development, and Job Insecurity on Employee Turnover Intention at PT Patra Jasa in Surabaya. The method used is a quantitative method with a total of 55 respondents who are employees of PT Patra Jasa in Surabaya. The data collection technique is by administering questionnaires and testing or analysis using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. The results of this research are that Meaningful Work cannot contribute to Turnover Intention. While Career Development and Job Insecurity can contribute to Turnover Intention, apart from that Meaningful Work and Job Insecurity can contribute to Career Development.